ELEMENTARY GAMES IN FUNCTION OF SPEED REACTION DEVELOPMENT OF YOUNG MALE AND FEMALE TEAM HANDBALL PLAYERS - Katarina Ohnjec; Maja Horvatin - Fučkar; Igor Gruić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Because of simply defined rules and concretely defined aim directionality, elementary games have important representation in contents of training process of young male and female team handball players. Development trends of handball game, regarding basic motor abilities, emphasise all segments of speed (speed reaction, singular movement speed, start and start acceleration). Team handball game effectiveness is significantly defined by basic reaction ability i.e. reactibility, therefore it is important to set it in the function of its manifestation during the performance of some - technical elements in specific situations. This paper presents the set of elementary games with the main focus on speed reaction regarding particular handball game - segments ("Let him shoot" "Throwing the ball against the wall", "Who is the fastest?", "Grasshopper", "Blocking", "Buzz", "Put the ball behind the line", "Pairs fighting for the ball", "Quick counter-attack", etc.).